The Role of Coaching In Enhancing The Completeness of Nursing Care Documentation - Rozi, Muhammad Fachrur; Wahidi, Kemala Rita; Pamungkas, Rian Adi (International Journal of Nursing and Health Services (IJNHS), 2025)
Abstract. This study was based on preliminary research indicating that the average completeness of nursing documentation in the inpatient unit was around 57.32%. The study aimed to examine coaching on mediating the knowledge and motivation on the completeness of nursing documentation. The cross-sectional study was employed in this study. We recruited the 121 inpatient nurses from Sultan Sulaiman hospital. Data collection was performed using questionnaires, and the analysis methods employed were the three-box method and SEM-PLS. The results show Fcount 150,320 > Ftable 2,68 indicated that knowledge, motivation, and coaching simultaneous influenced the completeness of nursing and result show path coefficient values 0,348 (positive) 0,195 (positive) and 0,417 (positive), which means that knowledge, motivation and coaching have an effect completeness of nursing care documentation individually. . Furthermore, coaching acted as a mediator, enhancing the impact of knowledge and motivation on documentation completeness. Therefore, the hospital needed to focus on improving nurses' knowledge and motivation through effective and sustainable coaching programs to enhance the quality of nursing documentation.